Mathematical modeling of hydrodynamic characteristics in the inlet of a reversible hydraulic machine based on mathematical models - Drankovskiy, Viktor Eduardovich; Rezvaya, Kseniya Sergeevna (НТУ "ХПИ", 2017)
Mathematical models that allow determining the hydrodynamic flow characteristics in the inlet of reversible hydraulic machines are considered. The features of the fluid flow are described. An analysis of the operating conditions of a reversible hydraulic machine, carried out during the design of the water passage, is made. Types of energy losses, taking into account the spatial effects of a viscous fluid, are determined. A group of mathematical models, oriented at different stages of design, is developed. A new way to the design of the water passage based on the experimental results is proposed. Specific programs for the design of the water passage of reversible hydraulic machines are considered. Features of mathematical models are defined.

Рассмотрено математические модели, которые позволяют определять гидродинамические характеристики потока в подводящей части обратимых гидравлических машин. Описаны особенности потока жидкости в подводящей части обратимой гидравлической машины. Производен анализ условий рабочего процесса обратимой гидравлической машины, осуществляемый в процессе проектирования проточной части. Определены виды потерь энергии с учетом пространственных эффектов вязкой жидкости. Разработана группа математических моделей, ориентированных на различные стадии проектирования. Определены особенности математических моделей.
Математическое моделирование гидродинамических характеристик в подводящей части обратимой гидромашины на основе математических моделей
Keywords: mathematical modeling; numerical research; hydrodynamic characteristics; inlet; wicket gate; spiral casing; coefficient of resistance; математическое моделирование; численное исследование; гидродинамические характеристики; подводящая часть; направляющий аппарат; спиральная камера; коэффициент сопротивления